Low-velocity impact resistance of double arrowhead triangular structure with negative Poisson’s ratio - Xinting, Liu; Wei, Luo; Feiyan, Xu; Yahui, Yang; Yangbo, Li (Frontiers in Materials, 2025)
Negative Poisson’s ratio (NPR) structures, known for their high specific strength, high specific stiffness, high impact resistance, etc., have broad applications in aerospace, medical equipment, transportation, shipping, sports, and other fields. Among them, the double arrowhead triangular structure with NPR effect has been proposed and designed, showing great potential for practical use. To study the properties of the double arrowhead triangular structure, Poisson’s ratio and low-velocity impact resistance of this structure have been calculated by numerical theory and finite element analysis. These methods provide a reliable way to evaluate the mechanical behavior of the structure under different conditions. The analysis of the double arrowhead triangular board structure has revealed the impact failure mode, impact velocity history curves, and the distribution of the first principal stress. Importantly, the results show that when the specific angles are α = 20° and β = 50°, the Poisson’s ratio of the double arrowhead triangular structure reaches − 2.1, and the low-velocity impact resistance of the structure is found to be the strongest at this angle combination. The findings of this study reveal the mechanism of low-velocity impact resistance of the double arrowhead triangular board structure and the influence of angle parameters on its impact performance. This understanding not only contributes to the theoretical knowledge of NPR structures but also broadens the engineering applications of double arrowhead triangular structures and NPR structures as a whole.